Specific alteration of rhythm in temperature-stressed rats possess features of abdominal pain in IBS patients - Yasuo Itomi; Toru Kawamura; Yasuhiro Tsukimi (Elsevier, 2015)
It is known that specific alteration of rhythm in temperature (SART) stress produces somatic pain. However, it remains to be investigated whether SART stress induces visceral pain. In this study, we investigated the visceral hypersensitivity in the SART stress model by pharmacological tools and heterotopical nociception. Four-week-old Sprague-Dawley rats were exposed to repeated cold stress. Visceral pain was measured by visceromotor response to colorectal distension, and the effects of alosetron and duloxetine on visceral pain were investigated in SART rats. Heterotopical nociception was given by capsaicin injection into the left forepaw to induce diffuse noxious inhibitory controls (DNIC). SART stress induced visceral hypersensitivity that was sustained at minimum for one week. In pharmacological analysis, alosetron and duloxetine improved SART stress-induced visceral hypersensitivity. Heterotopical nociception induced DNIC in normal conditions, but was disrupted in SART rats. On the other hand, RMCP-II mRNA in distal colon was not affected by SART stress. In conclusion, SART rats exhibit several features of visceral pain in IBS, and may be a useful model for investigating the central modification of pain control in IBS.